2010
DOI: 10.2220/biomedres.31.71
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity in venom proteins of the Russell's viper (Daboia russellii russellii) and the Indian cobra (Naja naja) in Sri Lanka

Abstract: To examine the molecular diversity of the venom proteins of the Russell's viper (Daboia russellii russellii) and the Indian cobra (Naja naja) in Sri Lanka, we isolated 38 venom proteins through a combination of anion exchange chromatography followed by reversed-phase high performance liquid chromatography. From the venom of D. r. russellii we isolated 15 proteins: 5 isozymes of phospholipase A 2 (PLA 2 ), 4 serine proteases, 2 C-type lectin-like proteins, 2 l-amino acid oxidases, 1 cysteine-rich secretory prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The partial primary structure of Rv(i) PLA 2 was determined by peptide mass fingerprinting, which revealed that it belongs to group II PLA 2 family. It is a D49 PLA 2 that showed sequence similarity with basic PLA 2 (P86368) reported from Sri Lankan D. russelii whose functional property has not been revealed . Rv(i) PLA 2 , a calcium‐dependent enzyme, exhibited high catalytic activity when diheptanoyl‐thiophosphatidylcholine was used as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The partial primary structure of Rv(i) PLA 2 was determined by peptide mass fingerprinting, which revealed that it belongs to group II PLA 2 family. It is a D49 PLA 2 that showed sequence similarity with basic PLA 2 (P86368) reported from Sri Lankan D. russelii whose functional property has not been revealed . Rv(i) PLA 2 , a calcium‐dependent enzyme, exhibited high catalytic activity when diheptanoyl‐thiophosphatidylcholine was used as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…UNC93A and SV seem to play a role in virus assembly and/or budding from the infected cell as revealed by transient gene silencing of SV2 or UNC93A in mosquitoes infected with SINV [37]. CRVP proteins are known to contain a trypsin inhibitor-like (TIL) domain, and therefore could be functioning as serine protease inhibitors [39]. One of the Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal sequence of the first 50 amino acids of the toxin ‘P1’ [31] and the N-terminal sequence of first 21 amino acids of the toxin PLA 2 4 [32] are a 100% match for the sequence of U1-viperitoxin-Dr1b. Following the suggested rational nomenclature for toxins [41], and given that the 94% sequence homology of the toxin with U1-viperitoxin-Dr1a[33], we have named the above toxin as U1-viperitoxin-Dr1b (Fig 6).…”
Section: Discussionmentioning
confidence: 99%
“…Myotoxic PLA 2 s cause muscle damage primarily by destruction of the sarcolemma [12,30]. Several PLA 2 toxins have been isolated from Sri Lankan Russell’s viper venom and biochemically characterised, [31,32] Some of these PLA 2 toxins contain a unique Serine residue at the N-terminus (S-type), while others have an Asparagine residue at the N-terminus (N-type) [32]. We have recently shown that the pre-synaptic neurotoxicity of the Sri Lankan Russell’s viper venom is primarily due to one of the S-type PLA 2 toxins, which we named U1-viperitoxin-Dr1a [33].…”
Section: Introductionmentioning
confidence: 99%